On the ethics of healthy ageing: setting impermissible trade-offs relating to the health and well-being of older adults on the path to universal health coverage - Kebadu Mekonnen Gebremariam; Ritu Sadana (BMC, 2019)
Abstract This article aims to clarify the moral underpinning of the policy framework of Healthy Ageing. It is a policy adopted by the World Health Organization designed to operate in alignment with the United Nations (UN) framework of the Sustainable Development Goals (SDGs) and the urgency given for the achievement of Universal Health Coverage (UHC). It particularly reflects on what, if anything, justifies protecting the most basic rights to health and well-being of older adults from possible policy trade-offs on the path to UHC. It argues that the dignity of older adults-under which are nested more specific ideas of self-respect, respect for autonomy, as well as the ethical priority for living well-underpins a categorical moral injunction against imposing the familiar utilitarian calculus as the default criterion for policy trade-offs across age groups. Respect for the dignity of older persons marks the moral threshold that every society ought to uphold even under conditions of relative resource scarcity. The moral constraint on permissible policy trade-offs relating to the health of older adults must reflect an understanding of older persons as active agents in the social structure of (their) well-being, not merely as passive vessels through which a good healthy life may or may not occur. We argue that there are three main domains where trade-offs are unacceptable from the moral point of view: it is impermissible (1) to prioritise key service(s) across different (vulnerable) age groups on the basis of actual or future contribution to society, (2) to prioritise across different age groups when co-prioritisation is warranted by the ethical theory, and (3), to always prioritise (by default) services that improve well-being over those that foster respect for dignity and autonomy.